Determinants influencing consumer preference towards imitation brand: A study among undergraduate students of UiTM (Melaka) City Campus / Nor Syafarin Norsin - Nor Syafarin Norsin (Faculty of Business Management, 2017)
This study is intends to investigate the factors influencing consumer preference on brand imitation (CPIB) among undergraduate students of UiTM Melaka City Campus.. Six objectives have been determined in this study. First, to identify the relationship between product involvement and CPIB Second, to identify the relationship between product familiarity and CPIB. Third, to identify the relationship between brand sensitivity and CPIB. Next, to identify the relationship between brand loyalty and CPIB. Fifth, to identify the relationship between price sensitivity and CPIB. Lastly, to identify the most factor that influence on CPIB. The population of the study consists of 1800 Bachelor Degree students, whilst the sample consists of 280 respondents from six course, International Business, Marketing, Finance, Human Resource, Office Management and Hotel and Tourism. The data were collected by distributing 317 questionnaires, and 280 respondents were returned the questionnaires. Therefore, only 280 questionnaires were used in this study. To analyse the data, descriptive, correlation and regression analyses were used. From the correlation analysis conducted, the results revealed that there are significant positive relationships between all independent variables (product involvement, product familiarity, brand sensitivity, brand loyalty, and price sensitivity) and dependant variable (CPIB). Meanwhile, from regression analysis conducted, it was found that brand loyalty gave more influence to CPIB. Last but not least, from the Model Summary derived from the analysis, it showed that all independent variables have major influence on CPIB by 90.2% and another 9.8% was influenced by the other factors.